1999
DOI: 10.1021/jp9906076
|View full text |Cite
|
Sign up to set email alerts
|

On the Rate Constant for the Association Reaction H + CN + Ar → HCN + Ar

Abstract: The importance of the chaperon mechanism (via ArCN or ArH complex formation) is investigated for the title reaction. All calculations employ the classical trajectory method to obtain the reactive cross sections while the equilibrium constants are estimated from statistical mechanics. A detailed analysis of the various approximations to the equilibrium constant is presented. Exploratory calculations based on the energy transfer mechanism are also reported. In addition, the decay rates of the HCN* and ArCN* spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…2.3 Kinetic Models. In previous work, , we described non-RRKM behavior by assuming the following two-step mechanism: where B (C) stands for a molecular species not coupled (strongly coupled) with the reaction path, and the rate coefficients (denoted k 3 and k 4 to be consistent with the notation used in the present work) follow the relation k 3 < k 4 or k 3 ≪ k 4 . The calculated fraction of nondissociated species at each moment was then fitted to the form 31 where f B and f C are the fractions of B and C at time t , and and are the corresponding values for t = 0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2.3 Kinetic Models. In previous work, , we described non-RRKM behavior by assuming the following two-step mechanism: where B (C) stands for a molecular species not coupled (strongly coupled) with the reaction path, and the rate coefficients (denoted k 3 and k 4 to be consistent with the notation used in the present work) follow the relation k 3 < k 4 or k 3 ≪ k 4 . The calculated fraction of nondissociated species at each moment was then fitted to the form 31 where f B and f C are the fractions of B and C at time t , and and are the corresponding values for t = 0.…”
Section: Methodsmentioning
confidence: 99%
“…2.3 Kinetic Models. In previous work, 31,32 we described non-RRKM behavior by assuming the following two-step mechanism:…”
Section: Potential Energy Surfacementioning
confidence: 99%
“…Both the momentum vector (p) and the inverse of the metric tensor (g~1) can also be written in partitioned form. In particular, p can be partitioned as pT \ (PT, JT) (35) where P is the momentum conjugate to Q, PT \ (P…”
Section: Appendixmentioning
confidence: 99%
“…Furthermore, due to its fundamental importance, several reaction dynamics studies involving HCN have been reported. [21][22][23][24] The most recent potential energy surface for HCN comes from the work of van Mourik et al, 13 who have based it on a fit to highly accurate ab initio data. Several analytical or semianalytical HCN/HNC potential energy surfaces had, however, been reported previously, 1,2,[25][26][27] some of which by explicitly fitting spectroscopic data.…”
Section: Introductionmentioning
confidence: 99%
“…It is also well established that HCN plays a key role in the combustion chemistry of nitrogen species, , where new reaction routes involving this molecule continue to be discussed (see, e.g., ref ). Furthermore, due to its fundamental importance, several reaction dynamics studies involving HCN have been reported. …”
Section: Introductionmentioning
confidence: 99%